nPal/E3SM:MPAS-Ocean Tidal Dynamics in Presence of Ice Shelf Cavities, in a Barotropic Ocean - Pal, Nairita; Barton, Kristin; Petersen, Mark; Brus, Steven R.; Engwirda, Darren; Arbic, Brian; Roberts, Andrew F.; Westerink, Joannes J.; Wirasaet, Damrongsak (Zenodo, 2022)
This is the archive of MPAS-Ocean code base (within E3SM) to study global barotropic tides in presence of Antarctic Ice Shelf Cavities